1989
DOI: 10.1099/00221287-135-2-273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Purine Hydroxylase I from Aspergillus nidulans

Abstract: Purine hydroxylase I from Aspergillus nidulans was purified 850-fold. The purified preparations exhibited the spectral and catalytic properties, including broad specificity for oxidizing and reducing substrates, typical of molybdenum/flavin/iron-sulphur-containing hydroxylases (oxotransferases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…For example, several genes for the basic generation of energy via glycolysis, the tricarboxylic acid cycle, and the pentose phosphate cycle were found, such as the genes coding for transketolases and transaldolases from the pentose phosphate cycle; glucose-6-phosphate dehydrogenases, fructose-1,6-bisphosphate dehydrogenase, and pyruvate carboxylases from the glycolysis process; and malate dehydrogenase and an aconitate hydratase from the tricarboxylic acid cycle. Five genes (2%) were found that are probably involved in the utilization of alternative nitrogen sources, including genes encoding the proline oxidase catalyzing the degradation of proline to glutamate (83), a choline oxidase, two xanthine oxidases responsible for the degradation of xanthine to urea (38,65), and an ␥-aminobutyrate transaminase catalyzing the formation of succinate semialdehyde and glutamate (57). , genes without significant expression changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several genes for the basic generation of energy via glycolysis, the tricarboxylic acid cycle, and the pentose phosphate cycle were found, such as the genes coding for transketolases and transaldolases from the pentose phosphate cycle; glucose-6-phosphate dehydrogenases, fructose-1,6-bisphosphate dehydrogenase, and pyruvate carboxylases from the glycolysis process; and malate dehydrogenase and an aconitate hydratase from the tricarboxylic acid cycle. Five genes (2%) were found that are probably involved in the utilization of alternative nitrogen sources, including genes encoding the proline oxidase catalyzing the degradation of proline to glutamate (83), a choline oxidase, two xanthine oxidases responsible for the degradation of xanthine to urea (38,65), and an ␥-aminobutyrate transaminase catalyzing the formation of succinate semialdehyde and glutamate (57). , genes without significant expression changes.…”
Section: Resultsmentioning
confidence: 99%
“…Potential AreA-dependent transporters include the three ammonium permeases mentioned above and several amino acid and peptide transporters as well as permeases of other nitrogen compounds ( Table 2, category IIc). Four genes whose products may be involved in nitrogen and carbon metabolism include the glutamine synthetase (GS)-encoding gene glnA (75); a gene coding for the xanthine dehydrogenase, which is responsible for the utilization of xanthine as an alternative nitrogen source (38,65); and a glycerol dehydrogenase and a phosphatidyl transferase, probably involved in carbohydrate metabolism. Finally, this group also contained genes likely involved in secondary metabolite production.…”
mentioning
confidence: 99%
“…Two enzymes of the XDH family have been described in A. nidulans. Purine hydroxylase I (PHI, HxA encoded by the hxA gene) is a typical XDH [7][8][9]. Purine hydroxylase II (PHII, HxnS; see below) has unprecedented substrate & 2017 The Authors.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we mined six genes for xanthine dioxygenase (XDO) based on the gene annotations. XDO can catalyze both hydroxylation of hypoxanthine to xanthine and hydroxylation of xanthine to uric acid 24,25 . XDO is a fungal enzyme that lacks a molybdopterin cofactor but is dependent on α-ketoglutarate and has the TauD motif 25 .…”
Section: Resultsmentioning
confidence: 99%